Immunohistochemical Expression of Differentiated Embryonic Chondrocyte 1 and Cluster of Differentiation 44 in Oral Potentially Malignant Disorders - Bianca-Andreea Onofrei; Delia Gabriela Ciobanu Apostol; Mădălina-Gabriela Tanasă; Elena-Raluca Baciu; Cristina Popa; Ana Maria Sciuca; Mihaela Paula Toader; Victor-Vlad Costan (Medicina)
Background and Objectives: Oral cancer remains a critical global health concern, with oral squamous cell carcinoma (OSCC) being the most prevalent form. Oral potentially malignant disorders (OPMDs), such as oral leukoplakia (OLK), oral lichen planus (OLP), and actinic cheilitis (AC), often precede OSCC. Identifying reliable biomarkers is vital for assessing malignant transformation risk. The present study aimed to evaluate the immunohistochemical expression of differentiated embryonic chondrocyte 1 (DEC1), a marker of dysplasia severity, and cluster of differentiation 44 (CD44), which is associated with cancer progression, in OPMD and OSCC tissues. Materials and Methods: A retrospective analysis was conducted on 145 biopsy specimens from January 2015 to January 2023, comprising normal mucosa (NM), OLK, OLP, AC, and OSCC. DEC1 and CD44 expression levels were assessed using immunohistochemical staining. Positivity scores were determined based on staining intensity and extent, with statistical analyses performed using SPSS software (SPSS Inc., Chicago, IL, USA, version 29.0 for Windows). Results: It was found that CD44 expression significantly increased across OPMD and OSCC compared to NM (p < 0.001). Conversely, DEC1 expression was consistent across lesion types and dysplasia levels. CD44 expression was the highest in AC and OSCC, underscoring its potential role as a progression marker. Conclusions: The results indicate that CD44 is a more sensitive marker for assessing dysplastic severity and malignant transformation, while DEC1 may serve as a complementary marker for early-stage evaluation. Further research involving larger cohorts is needed to confirm these findings.